Non-fatal paliperidone overdose: A case report - Gill, J.S.; Pillai, S.K.; Koh, O.H.; Jambunathan, S. (Turkiye Sinir Ve Ruh Sagligi Dernegi, 2010)
Paliperidone, a novel serotonin and dopamine antagonist, is one of the newest atypical antipsychotics on the market. It is an orally administered drug that is indicated for the treatment of schizophrenia, and is considered to be safe and well tolerated. A 37-year-old female with a long-standing history of schizophrenia had been taking paliperidone 12 mg d-1 for about 1.5 years. She overdosed on a total of 756 mg of paliperidone in response to auditory command hallucinations. She was promptly hospitalized, and fortunately did not suffer any major adverse clinical events, adverse laboratory parameters, or long lasting sequelae. Herein we discuss the inherent characteristics of paliperidone that limit the danger associated with overdosing.